RANCANG BANGUN APLIKASI E-ELECTION PRESIDEN MAHASISWA BERBASIS PHP PADA UNIVERSITAS UBUDIYAH INDONESIA - MULIADI, M. (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
Technological developments are evolving at this time has driven the acceleration in variousfields. This also caused the emergence of advances in software, are offset by advances and technologicalsophistication along with the hardware. Presidential Election University Students Ubudiyah Indonesia(UUI) is part of the democratic process, where students can choose directly by using an application thatwould be designed. During the Presidential election in 2014 is still used manually in a paper ballot intothe conduct of elections in the choice of President of the Students. The research used the qualitativemethods of collecting, compiling, classifying the data with a view to introducing or developing anapplication system E-Election presidential elections, so that the application easier to use by students. Theresult of this research is that when the student has chosen the voting rights of the candidates for Presidentand Vice President of the Students can no longer do the selection of the candidates for President and VicePresident of the Students. This application displays the results of the vote counting process using thegraphics system, to facilitate the students for the Presidential election in the elections, so that no fraud invote counting.